Peran Ekologis Serangga Terbang Diurnal untuk Pertanian dan Potensinya untuk Kolaborasi Pendidikan Biologi - Hery Fajeriadi; Bimo Aji Nugroho; Fahmi Fahmi; Riza Arisandi (Jurnal Penelitian Pendidikan IPA, 2025)
The quality of agriculture is affected by insects in agricultural areas. Both insects that have a negative impact such as pests, positive such as predators against pests, and those that are neutral or have no effect on agriculture, but can be an indicator of the ecosystem. Control of plant pest organisms (PPO) is often done by spraying pesticides, but also results in a decrease in the population of insect predators of pests. The diversity of flying insects in Haturak farm, Kupang Village, Tapin Regency has not been documented. This study aims to identify the types of flying insects on Haturak farm and analyze their ecological role. The research method used was a descriptive and observational approach. Data were collected through total roaming and direct documentation using macro photography in the insects’ natural habitat. Analysis was done descriptively and reinforced with literature studies. The results of the study found 18 species of flying insects from six orders. Eight species played a positive role, while ten species had a negative impact on agriculture. Among them, two species played both positive and negative roles, and two others had a neutral role. This condition is less favorable for agriculture because there are fewer predatory insect species than pests. For the sake of biological pest control, enriching pest predator species is recommended to reduce land damage due to high or frequent chemical use. Further studies on diversity and abundance indices are recommended to understand the territorial dominance of each species, as well as to evaluate the effectiveness of biological control. Collaboration between Biology Education and farmers through ecological education builds synergy between science and sustainable farming. The five initiatives enhance ecological literacy and apply local wisdom. To maximize impact, it is recommended to integrate these programs into regular academic and community service activities, ensuring long-term engagement and measurable outcomes.